Upaya Pengendalian Kualitas pada Proses Produksi Roti Tawar dengan Statistic Process Control (SPC) dan Failure Mode and Effects Analysis (FMEA) (Studi Kasus Pabrik Roti RV) - Wahyudi, Rizqi; Vebriyanti, Ria (Jurnal Engine: Energi, Manufaktur, dan Material, 2025)
RV Bakery faces challenges in maintaining product quality due to fluctuating defect rates, particularly in white bread production. This issue has the potential to undermine customer trust and result in market losses. This study aims to analyse defect levels, identify the root causes of defects, and develop corrective solutions to reduce product defects. The methods employed include Statistical Process Control (SPC) to statistically monitor production process variations and Failure Modes and Effects Analysis (FMEA) to prioritize corrective actions based on Risk Priority Number (RPN) values. The 5W+1H approach was used to formulate improvement steps. The analysis results revealed that burnt defects dominated at 78% compared to collapsed defects at 22%. Through control charts, it was found that burnt defects exceeded the Upper Control Limit (UCL) at two points, specifically on October 15 and 17, 2024. The root causes of defects were identified using a cause-and-effect diagram, encompassing human, material, machine, and method factors. Corrective measures included adjusting baking time using timers, utilizing thermometers to ensure stable oven temperatures, and implementing stricter Standard Operating Procedures (SOP). The implementation of these improvements significantly reduced the number of defective products, with defect rates consistently remaining within control limits.